If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = 6x + 24 Reorder the terms: -4 + 2x = 6x + 24 Reorder the terms: -4 + 2x = 24 + 6x Solving -4 + 2x = 24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 2x + -6x = 24 + 6x + -6x Combine like terms: 2x + -6x = -4x -4 + -4x = 24 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -4x = 24 + 0 -4 + -4x = 24 Add '4' to each side of the equation. -4 + 4 + -4x = 24 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = 24 + 4 -4x = 24 + 4 Combine like terms: 24 + 4 = 28 -4x = 28 Divide each side by '-4'. x = -7 Simplifying x = -7
| 8s^2-10st-3t^2=0 | | .35+.03=.45+.02 | | (n-1)/2=35 | | 0.3x+0.6(25-x)=12 | | y=5/3x-7 | | 1-7b-10b= | | 169x^2-196x^2= | | 4x^2+3x^2+2x= | | (x/4)-(x/8)+7=x+7 | | 3y^2+2y-14=0 | | .83+1=-.50+.25 | | y=5/7x-12 | | a=5/9+2/4 | | 9x+91=7-5x | | 4(5+8)= | | .25x-7=.125(2x+8) | | 7-8x=9x+7 | | (5x+1)=(2x-3) | | 9+3(2x+4)=33 | | 6-7x=5x-8x-2 | | px-4=q | | x/0.9=8.9 | | .01(x+5)-.5=.1(6x+5) | | y=-4.9x+10.9 | | 4x+190=300 | | 3(x+6)=5x+22 | | x^2-1x+2=0 | | 6(1+x)=-6+8x | | 100x=150 | | x^2+2x-6=20 | | 14-x=2x-1 | | .01(x+7)-.7=.1(8x+7) |